(untitled) (Research, Society and Development, 2022)
Safe and patient-centered care is a relevant and current topic. Objective: To analyze the use of Foucault’s concepts in Brazilian theses and dissertations that address patient safety, their participation and their involvement in care. Methodology: Qualitative, descriptive, documentary study, through a survey and characterization of Brazilian theses and dissertations, available on the website of the Theses and Dissertations Catalog of the Coordination for the Improvement of Higher Education Personnel, using the strategy based on the terms "Safety OR Patient Centrality OR Patient Participation AND Foucault”, 50 studies were located, 12 were not available as full text and 30 did not meet the objective, 08 studies were selected for full reading, and included for data analysis. Results: It was possible to identify that the selected studies refer to one or more Foucauldian concepts and even use different concepts from the archaeological and genealogical phase simultaneously, so five studies emerged concepts from the archaeological phase, and seven from the genealogical phase. Final considerations: Political relations in hospital institutions are often treated subtly, but they exist. Relating knowledge, power, norm, discipline and health ethics, from the perspective of the philosopher Michel Foucault’s concepts, allow us to perceive nuances of care that often go unnoticed in everyday life. Patient safety is not clearly addressed in the analyzed texts, but it was possible to identify the authors’ concern with safe care and patient participation in care.